2001
DOI: 10.1177/152574010102200405
|View full text |Cite
|
Sign up to set email alerts
|

Conversations with Mexican Americans Regarding Children with Disabilities and Augmentative and Alternative Communication

Abstract: Focus groups consisting of seven family members of children with disabilities provided information for identifying and understanding issues influencing augmentative and alternative communication (AAC) practices within a Mexican American community. The authors used a content analysis of the conversations to identify seven general perspectives: (a) Children understand the nonverbal communication of persons around them; (b) aided techniques are useful outside of the home; (c) families have great respect for profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 19 publications
1
29
0
1
Order By: Relevance
“…The children in the study had no motor impairments (except for their speech), and receptive language skills were within normal limits. It is possible, then, that the results from the investigation may not generalize to other Latino populations (Huer et al, 2001) or to children who use AAC who have different profiles (e.g., cognitive delays, receptive language impairments, severe motor impairments). However, it is very encouraging to note that a very similar version of the instructional program has been shown to increase the turn-taking skills of children with different profiles, including children with severe speech and physical impairments and children with cognitive delays (Kent-Walsh, 2003;Kent-Walsh et al, 2004).…”
Section: Limitationsmentioning
confidence: 83%
See 1 more Smart Citation
“…The children in the study had no motor impairments (except for their speech), and receptive language skills were within normal limits. It is possible, then, that the results from the investigation may not generalize to other Latino populations (Huer et al, 2001) or to children who use AAC who have different profiles (e.g., cognitive delays, receptive language impairments, severe motor impairments). However, it is very encouraging to note that a very similar version of the instructional program has been shown to increase the turn-taking skills of children with different profiles, including children with severe speech and physical impairments and children with cognitive delays (Kent-Walsh, 2003;Kent-Walsh et al, 2004).…”
Section: Limitationsmentioning
confidence: 83%
“…AAC use and culture. Participants discussed the fact that some Latino families may believe that their children communicate functionally at home and may resist having their children use AAC devices in the home, a finding that is supported by Huer and colleagues (Huer, Parette, & Saenz, 2001). To address this issue, one participant suggested that AAC devices should be introduced as something that ''will help your child with school''; all participants agreed that this was a good approach for introducing AAC.…”
Section: Discussionmentioning
confidence: 94%
“…Traditionally, the subject of cultural and linguistic diversity has been neglected in the AAC field (Light, 1997). Only recently has the literature addressed this subject area with regard to AAC assessment (e.g., Huer, 1997), intervention (e.g., Huer, Parette, & Saenz, 2001), service delivery (e.g., Parette, Huer, & Brotherson, 2001), and research (e.g., Huer & Saenz, 2002).…”
Section: Cultural Differencesmentioning
confidence: 98%
“…For example, Asian family members may want to see immediate results if an electronic speech device is provided for their child, without regard to the amount of training that may be required to effectively use the device (Huer, 1999a(Huer, , 1999b; see box, "Case Study 3"). A Hispanic family may want the child to immediately be able to use the device at an important family celebration (e.g., the quincancera; Huer, Parette, & Saenz, 2001). After an assistive technology evaluation is conducted, it may become apparent that the child can effectively use a device, yet the family is told that the funding process may take weeks or months before the child will receive the device.…”
Section: What Are the Family's Expectation For Child Independence?mentioning
confidence: 99%